Time-related bond strength of resin-reinforced glass ionomer cement under various light exposure conditions. Issue 3 (September 2015) - Fukino, Yoshitaka; Komori, Akira
Abstract Purpose This study's purpose was to determine the time-related bond strengths of light-cured resin-reinforced glass ionomer cement (LCGIC) under various conditions of light exposure. Materials and methods 480 freshly extracted bovine mandibular incisors were randomly divided into 32 groups. The study was performed in 4 light curing conditions, at 4 bond-testing times, and by 2 bond testing methods. For dental curing lights, LED using a source consisting of high intensity light-emitting diode, TQH (tungsten quartz halogen lamp) and PAC (plasma arc lamp) were used. Light exposure from 2 directions was performed under 4 conditions: for 5 s with LED (LED-5s), for 10 s with LED (LED-10s), for 20 s with TQH, and for 3 s with PAC. Tensile and shear bond tests were performed at 4 time-points after light exposure, i.e. 0 min, 3 min, 30 min, and 24 h. Results LED had the highest peak output by 44.7 mW/cm2 at 458 nm. Significant increase over time of tensile and shear bond strength was observed in all of the groups. TQH and PAC had low tensile bond strength just after the exposure. LED-10's demonstrated significantly higher tensile and shear bond strength compared with other groups. Conclusion Although LED and PAC showed approximately peak irradiance five times higher than TQH, there is no significant difference in tensile and shear bond strength between TQH and PAC. It appears that LCGIC would have provided greater bond strength under various conditions of LED-10's.